A novel verification method using a plastic scintillator imagining system for assessment of gantry sag in radiotherapy. Issue 6 (9th May 2018) - Tsuneda, Masato; Nishio, Teiji; Saito, Akito; Tanaka, Sodai; Suzuki, Tatsuhiko; Kawahara, Daisuke; Matsushita, Keiichiro; Nishio, Aya; Ozawa, Shuichi; Karasawa, Kumiko; Nagata, Yasushi
Abstract : Purpose: High accuracy of the beam‐irradiated position is required for high‐precision radiation therapy such as stereotactic body radiation therapy (SBRT), volumetric modulated arc therapy (VMAT), and intensity modulated radiation therapy (IMRT). Users generally perform the verification of the mechanical and radiation isocenters using the star shot test and the Winston Lutz test that allow evaluation of the displacement at the isocenter. However, these methods are unable to evaluate directly and quantitatively the sagging angle that is caused by the weight of the gantry itself along the gantry rotation axis. In addition, the verification of the central axis of the irradiated beam that is not dependent at the isocenter is needed for the mechanical quality assurance of a nonisocentric irradiation technique. In this study, we have developed a prototype system for the verification of three‐dimensional (3D) beam alignment and we have verified the system concept for 3D isocentricity. Our system allows detection of the central axis in 3D coordinates and evaluation of the irradiated oblique angle to the gantry rotation axis, i.e., the sagging angle. Materials & Methods: In order to measure the central axis of the irradiated beam in 3D coordinates, we constructed the prototype verification system consisting of a column‐shaped plastic scintillator (CoPS), a truncated cone‐shaped mirror (TCsM), and a cooled charged‐coupled device (CCD) camera. This verification system was irradiated with 6‐MV photon beams and the scintillation light was measured using the CCD camera. The central axis on the axial plane (two‐dimensional (2D) central axis) was acquired from the integration of the scintillation light along the major axis of the CoPS, and the central axis in 3D coordinates (3D central axis) was acquired from two curve‐shaped profiles which were reflected by the TCsM. We verified the calculation accuracy of the gantry rotation axis, θ z . Additionally, we calculated the 3D central axis and the sagging angle at each gantry angle. Results: We acquired the measurement images composed of the 2D central axis and the two curve‐shaped profiles. The relationship between the irradiated and measured angles with respect to the gantry rotation axis had good linearity. The mean and standard deviation of the difference between the irradiated and measured angles were 0.012 and 0.078 degrees, respectively. The size of the 2D and 3D radiation isocenters were 0.470 and 0.652 mm on the axial plane and in 3D coordinates, respectively. The sagging angles were −0.31, 0.39, and 0.38 degrees at the gantry angles of 0, 180, and 180E degrees, respectively. Conclusion: We developed a novel verification system, designated as the "kompeito shot test system, " to verify the 3D beam alignment. This system concept works for both verification of the 3D isocentricity and the direct evaluation of the sagging angle. Next, we want to improve the aspects of this system, such as the shape and the type of scintillator, to increase the system accuracy and nonisocentric beam alignment performance.